Exame comparativo das estratégias nacionais de inteligência artificial de Argentina, Brasil, Chile, Colômbia e Coreia do Sul: Consistência do diagnóstico dos problemas-chave identificados - Tulio Chiarini; Sérgio Amadeu da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Given the importance attributed to artificial intelligence (AI) and due to its transversal and pervasive nature, many governments worldwide have developed national AI strategies, in a movement of technological competition. So far, 56 countries, plus the European Union (EU), have more or less systematized documents that have been mapped by the OECD's AI Policy Observatory. Although there are studies that propose analyzes of these strategies from different perspectives and methodologies, there is still room in the literature to debate them from other points of view, especially based on the diagnosis of the key challenges identified in each of the documents. The countries examined in this Discussion Paper were Argentina, Brazil, Colombia, Chile, and South Korea. The strategies of the South American and South Korean group are not free of gaps in relation to the diagnosis of key problems: the strategies presented evidence-based diagnoses that were mostly insufficient and inconsistent, often using inadequate and even unsatisfactory proxies to subsidize them. The qualitative analyzes presented make a dual contribution to debates on national AI strategies. First, they give light to the State as a central actor in a field dominated by private governance arrangements, revealing the possibility of hybrid interactions. Second, they capture the variety of approaches taken by governments to respond to AI challenges, although the strategies of Argentina, Brazil, Chile and Colombia are in the wake of the global movement pulled by other countries.
10419/284861
Keywords: L52; O21; O25; O38; 330; strategy; artificial intelligence; public policy assessment